Organ-resolved lipid mapping in Steatoda nobilis spider model using high-resolution mass spectrometry imaging and Kendrick mass defect analysis - Redureau, Damien; Dunbar, J. P.; La Rocca, Raphaël; De Monts De Savasse, Axel; Bastiaens, Quentin; Bertrand, Virginie; Kune, Christopher; Tiquet, Mathieu; Far, Johann; De Pauw, Edwin; Dugon, Michel M.; Quinton, Loïc (Frontiers in Chemistry, 2025)
The noble false widow spider (Steatoda nobilis), a rapidly spreading member of the Theridiidae family, has gained attention for its increasing presence near human habitats and its medical significance due to envenomation reports. Recent studies have revealed that its venom contains α-latrotoxins, toxins also found in Latrodectus (black widows), responsible for latrodectism symptoms. Despite this growing interest, little is known about the lipidome and metabolome of S. nobilis, which could offer insights into its ecological role, dietary metabolism, and chemical communication. In this study, we used Matrix-Assisted Laser Desorption/Ionization Fourier-Transform Ion Cyclotron Resonance (MALDI-FT-ICR) mass spectrometry imaging (MSI) to investigate the whole-body lipid and metabolite distribution in S. nobilis. MSI is a powerful tool that couples molecular analysis with spatial information, enabling detailed visualization of biomolecules in tissues. Applying MSI to arachnids offers a novel approach to explore organ-specific metabolic profiles and identify potentially bioactive or adaptive compounds. One of the major challenges was preserving the spider’s fragile internal anatomy during sample preparation. We developed a gelatin-based fixation method to obtain intact histological sections suitable for MSI analysis. This allowed us to clearly distinguish organ-specific lipid and metabolite distributions in situ, including within the silk glands, ovaries, and nervous tissues. A second challenge was managing the vast data generated by MSI, with each image yielding thousands of molecular peaks. To streamline analysis, we employed Kendrick Mass Defect (KMD) plots to classify ions into structural families. This approach enabled us to link specific ions to molecular families and localize them within the spider’s body, enhancing our anatomical understanding at the molecular level. This work not only provides foundational insights into S. nobilis biochemistry but also demonstrates the potential of MSI for advancing arachnid lipidomics and uncovering molecules of ecological or biomedical interest. It opens the gates for broader applications of spatial lipidomics in other small biosystems and animals, particularly those previously inaccessible to detailed biochemical analysis.